Modeling the Impact of Viscosity on Fricke Gel Dosimeter Radiolysis: A Radiation Chemical Simulation Approach - Sumaiya Akhter Ria; Jintana Meesungnoen; Jean-Paul Jay-Gerin (Gels)
The Fricke gel dosimeter, a hydrogel-based chemical dosimeter containing dissolved ferrous sulfate, measures 3D radiation dose distributions by oxidizing Fe2+ to Fe3+ upon irradiation. This study investigates the variation in Fricke yield, G(Fe3+), from a radiation–chemical perspective in both standard and gel-like Fricke systems of varying viscosities, under low- and high-linear energy transfer (LET) conditions. We employed our Monte Carlo track chemistry code IONLYS-IRT, using protons of 300 MeV (LET~0.3 keV/µm) and 1 MeV (LET~25 keV/µm) as radiation sources. To assess the impact of viscosity on G(Fe3+), we systematically varied the diffusion coefficients of all radiolytic species in the Fricke gel, including Fe2+ and Fe3+ ions. Increasing gel viscosity reduces Fe3+ diffusion and stabilizes spatial dose distributions but also lowers G(Fe3+), compromising measurement accuracy and sensitivity—especially under high-LET irradiation. Our results show that an optimal Fricke gel dosimeter must balance these competing factors. Simulations with lower sulfuric acid concentrations (e.g., 0.05 M vs. 0.4 M) further revealed that G(Fe3+) values at ~100 s are nearly identical for both low- and high-LET conditions. This study underscores the utility of Monte Carlo simulations in modeling viscosity effects on Fricke gel radiolysis, guiding dosimeter optimization to maximize sensitivity and accuracy while preserving spatial dose distribution integrity.